Repurposing of the β-Lactam Antibiotic, Ceftriaxone for Neurological Disorders: A Review - Yimer, Ebrahim M.; Hishe, Hailemichael Zeru; Tuem, Kald Beshir (Frontiers in Neuroscience, 2019)
To date, there is no cure or disease-modifying agents available for most well-known neurological disorders. Current therapy is typically focused on relieving symptoms and supportive care in improving the quality of life of affected patients. Furthermore, the traditional de novo drug discovery technique is more challenging, particularly for neurological disorders. Therefore, the repurposing of existing drugs for these conditions is believed to be an efficient and dynamic approach that can substantially reduce the investments spent on drug development. Currently, there is emerging evidence that suggests the potential effect of a beta-lactam antibiotic, ceftriaxone (CEF), to alleviate the symptoms of different experimentally-induced neurological disorders: Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis, epileptic-seizure, brain ischemia, traumatic brain injuries, and neuropathic pain. CEF also affects the markers of oxidative status and neuroinflammation, glutamatergic systems as well as various aggregated toxic proteins involved in the pathogenesis of different neurological disorders. Moreover, it was found that CEF administration to drug dependent animal models improved the withdrawal symptoms upon drug discontinuation. Thus, this review aimed to describe the effects of CEF against multiple models of neurological illnesses, drug dependency, and withdrawal. It also emphasizes the possible mechanisms of neuroprotective actions of CEF with respective neurological maladies.